Avaliação da dinâmica estrutural do domínio variável de anticorpos de cadeia pesada única derivados de camelídeos (VHH) - Adan, Wenny Camilla dos Santos (2020)
Camelid-derived Heavy-chain antibodies (HCAb) use the N-terminal variable domain to establish interaction with the antigen. When Isolated, this domain is referred as VHH. Despite having half the size of the antigen recognition region of conventional antibodies, VHHs have equivalent specificity and affinity for antigens. In order to remain functional even with a small size, the VHHs have undergone evolutionary adaptations and the main modifications are concentrated in the complementarity determining region (CDR1-3), constituted mainly by loops, whose function is the recognition of the antigen. The information regarding the structural dynamics of these regions in view of the stability, flexibility and affinity of VHHs is still elusive and the understanding of the molecular bases involved in the VHH-antigen interaction can contribute to the rational design of synthetic antibodies. Through molecular dynamics simulations, the present study identified and characterized the structural dynamic profile of the CDR1-3 loops for 40 VHH structures. Contrary to what was expected, the amplitude of conformational diversity and flexibility are not correlated with the length of CDR loops. RMSF data regarding the CDR3 loop achieved a correlation of R2 = 0.71 with the experimental bind free energy (ΔG bind), indicating that an increase in the flexibility of this loop leads the VHHs to higher binding affinities. This information is unprecedented in the literature of VHHs and supersedes the hypothesis that the rigidity or flexibility of loops is only one of the biophysical mechanisms that VHHs use to increase affinity. Ramachandran plots showed a well-structured profile for CDR3, highlighting the presence of a characteristic region of α-helices. In fact, very long loops are known to have a tendency to modulate their C-terminal region. Finally, the construction of the solvent accessibility index (SAI) allowed the classification of the chemical character of the CDR regions, pointing out the identity of the residues and their propensity to confer specificity or assume structural functions.